The relationship between the capabilities, absorptive capacity and sustainable competitive advantage of small and medium enterprises (SMEs) in Malaysia - Nurul Huda Md Yatim (2021)
Small and medium enterprises (SMEs) in the service sector are currently facing major challenges in maintaining their sustainable competitive advantage (SCA) as the majority of them offer homogeneous products and services. This factor has led to rivalry and increasing competition among them. To investigate this issue, this study has examined the capability of information management (IMC), knowledge management (KMC), innovation (INC), and technology (TEC) – known as IKIT and the SCA of SMEs in Malaysia. As for recognition of the importance of SMEs to the economy, numerous government interventions have been implemented over the years, all of which have been aimed at the development of SMEs and sustaining their competitive advantage. However, the homogeneity of products and services offered by the service sector has resulted in a more competitive and dynamic business environment for all SMEs, which makes it even more challenging for these SMEs to prosper. This research also examined absorptive capacity (ABC) as a mediator and government intervention (GOI) as a moderator variable influencing the relationship between the IKIT and SCA of SMEs. A self-administered questionnaire was used to collect data from 210 SME firms in Peninsular Malaysia from 22 February until 25 May 2019, and the gathered data was analysed using SPSS 21.0 and SmartPLS version 3.2.8. The result shows that GOI and IKIT capabilities are not positively related and the relationship between them is not significant. The result shows that only knowledge capability (KMC), innovation capability (INC), and technology capability (TEC) are significantly related to the SCA of SMEs. Meanwhile, the finding of absorptive capacity portrays a significant mediating effect between both INC and TEC, although this is in no way significant for information management capability (IMC) for all relationships. Unfortunately, there is no interaction of GOI as a moderator on IKIT and SCA. One of the reasons is due to most of service sector firms are owner-managed and therefore are not under pressure to increase profit and turnover. The outcome of this study provides new knowledge and important insights for the government to look further into the programmes and guidelines, and to enforce new policies to improve the SCA of SMEs in Malaysia. The findings indicate that SMEs have the capability to accept any changes when it comes to innovation and technology, which helps in placing a firm in an advantageous position compared to its competitors. Based on the findings, the theoretical and practical implications of the study as well as limitations and recommendations for future studies are also discussed.